Stopping antibiotics after surgical amputation in diabetic foot and ankle infections—A daily practice cohort. Issue 2 (6th February 2019) - Rossel, Anne; Lebowitz, Dan; Gariani, Karim; Abbas, Mohamed; Kressmann, Benjamin; Assal, Mathieu; Tscholl, Philippe; Stafylakis, Dimitrios; Uçkay, Ilker
Summary: Objective: The appropriate duration of antibiotic therapy for diabetic foot infections (DFI) after surgical amputations in toto is debated. There are discrepancies worldwide. Methods: Using a clinical pathway for adult DFI patients (retrospective cohort analysis), we conducted a cluster‐controlled Cox regression analysis. Minimum follow‐up was 2 months. Results: We followed 482 amputated DFI episodes for a median of 2.1 years after the index episode. The DFIs predominately affected the forefoot (n = 433; 90%). We diagnosed osteomyelitis in 239 cases (239/482; 50%). In total, 47 cases (10%) were complicated by bacteremia, 86 (18%) by abscesses and 139 (29%) presented with cellulitis. Surgical amputation involved the toes (n = 155), midfoot (280) and hindfoot (47). Overall, 178 cases (37%) required revascularization. After amputation, the median duration of antibiotic administration was 7 days (interquartile range, 1‐16 days). In 109 cases (25%), antibiotics were discontinued immediately after surgery. Overall, clinical failure occurred in 90 DFIs (17%), due to the same pathogens in only 38 cases. In multivariate analysis, neither duration of total postsurgical antibiotic administration (HR 1.0, 95% CI 0.99‐1.01) nor immediate postoperative discontinuation altered failure rate (HR 0.9, 0.5‐1.5). Conclusion: According to our clinical pathway, we found no benefit in continuing postsurgical antibiotic administration in routine amputation for DFI. In the absence of residual infection (ie, resection at clear margins), antibiotics should be discontinued. Abstract : The continuation of systemic antibiotic therapy after amputation for diabetic foot infection/osteomyelitis is very common. In our cohort and clinical pathway of adult hospitalized diabetic foot infections, we evaluated the influence of the duration of postsurgical antibiotic prescription on different forms of clinical failures. The duration of postsurgical amputation was unrelated to failure if the amputation was performed in clinical non‐infected tissue/bone, leaving the possibility of massive shortening of this continuation of antibiotics.